2016
DOI: 10.1080/17470919.2016.1144646
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potentials reveal early attention bias for negative, unexpected behavior

Abstract: Numerous studies have documented that expectancy-violating (EV) behavior (i.e., behavior that violates existing person impressions) elicits more effortful cognitive processing compared to expectancy-consistent (EC) behavior. Some studies also have shown that this effect is modulated by the valence of behavior, though this finding is inconsistent with some extant models of expectancy processes. The current research investigated whether the valence of EV information affects very rapid attentional processes thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…Rewards help stimuli with insignificant features capture attention, even if the rewards subsequently disappear, or the stimulus is independent of the target (Wang, 2016), and when rewards are combined with distraction stimuli, the choice of goals may be hindered (Fan et al, 2014). Numerous studies have found attention biases toward negative stimuli in cognitive processes, which means that individuals detect negative, and threatening stimuli quickly (Jerónimo et al, 2017). Negative faces, especially threatening faces, attract attention, and prolong attention maintenance or reduce attention disengagement ability (Fox et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Rewards help stimuli with insignificant features capture attention, even if the rewards subsequently disappear, or the stimulus is independent of the target (Wang, 2016), and when rewards are combined with distraction stimuli, the choice of goals may be hindered (Fan et al, 2014). Numerous studies have found attention biases toward negative stimuli in cognitive processes, which means that individuals detect negative, and threatening stimuli quickly (Jerónimo et al, 2017). Negative faces, especially threatening faces, attract attention, and prolong attention maintenance or reduce attention disengagement ability (Fox et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to studies using the International Affective Picture System [5] or standard facial expressions [6], social neuroscientists have used sentences [7,8], paragraphs [9,10] and scripted imagery of social events [11]. Unfortunately, static and simplistic stimuli may not be representative of real-life social encounters, and tasks with static stimuli may result in ceiling effects [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the pioneering paradigms in social neuroscience reflect a noteworthy emphasis upon laboratory control and experiments that involve participants observing static stimuli (e.g., simple, static representations of socially relevant stimuli; static photographs of emotionally valenced facial expressions). In addition to studies using the International Affective Picture System [ 5 ] or standard facial expressions [ 6 ], social neuroscientists have used sentences [ 7 , 8 ], paragraphs [ 9 , 10 ] and scripted imagery of social events [ 11 ]. Unfortunately, static and simplistic stimuli may not be representative of real-life social encounters, and tasks with static stimuli may result in ceiling effects [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Turner et al ( 1987 ) showed that, when the behavior is consistent with the stereotype of a particular category (nominative fit), this category would be the dominant category, as the behavior information directs the perceiver to the stereotype-consistent category. However, a large number of studies since then have found that the perceiver pays attention to the target that contradicts the stereotype expectancy (Bettencourt et al, 1997 ; Dickter and Gyurovski, 2012 ; Garcia-Marques et al, 2016 ; Jerónimo et al, 2016 ). People engage in more effortful cognitive processing (Jerónimo et al, 2016 ), reorganize the “wrong description” (contradicting the expectancy), perceive the stereotype-inconsistent target as atypical, make more explanations about and prefer external attributions for the behavior (Sekaquaptewa et al, 2003 ; Sekaquaptewa and Espinoza, 2004 ), and make the stereotype-inconsistent behavior conform to their stereotype.…”
Section: Introductionmentioning
confidence: 99%
“…However, a large number of studies since then have found that the perceiver pays attention to the target that contradicts the stereotype expectancy (Bettencourt et al, 1997 ; Dickter and Gyurovski, 2012 ; Garcia-Marques et al, 2016 ; Jerónimo et al, 2016 ). People engage in more effortful cognitive processing (Jerónimo et al, 2016 ), reorganize the “wrong description” (contradicting the expectancy), perceive the stereotype-inconsistent target as atypical, make more explanations about and prefer external attributions for the behavior (Sekaquaptewa et al, 2003 ; Sekaquaptewa and Espinoza, 2004 ), and make the stereotype-inconsistent behavior conform to their stereotype. Furthermore, the shifting standards model suggests that the target is evaluated with reference to the stereotype expectations of that particular category; the perceiver makes extreme judgments (Biernat and Vescio, 2002 ) and uses ironic language more often in response to the target who behaves in a manner contrary to expectation (Burgers and Beukeboom, 2014 ), so as to maintain stereotypic expectancies.…”
Section: Introductionmentioning
confidence: 99%